Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12864-015-2074-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome, microRNA, and degradome analyses of the gene expression of Paulownia with phytoplamsa

Abstract: BackgroundPaulownia witches’ broom (PaWB) is a fatal disease of Paulownia caused by a phytoplasma. In previous studies, we found that plants with PaWB symptoms would revert to a healthy morphology after methyl methane sulfonate (MMS) treatment. To completely understand the gene expression profiles of the Paulownia-phytoplasma interaction, three high-throughput sequencing technologies were used to investigate changes of gene expression and microRNAs (miRNAs) in healthy Paulownia tomentosa plantlets, PaWB-infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 79 publications
1
32
0
Order By: Relevance
“…Reverse transcription and PCRs were performed to obtain sufficient single-stranded cDNA. The PCR procedure was conducted according to [23]. An Agilent 21.00 Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA) and ABI StepOnePlus Real-Time PCR System (Life Technologies, Grand Isle, NY, USA) were used to determine the quality and yield, respectively.…”
Section: Construction and Sequencing Of Small Rna And Degradome Libramentioning
confidence: 99%
See 2 more Smart Citations
“…Reverse transcription and PCRs were performed to obtain sufficient single-stranded cDNA. The PCR procedure was conducted according to [23]. An Agilent 21.00 Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA) and ABI StepOnePlus Real-Time PCR System (Life Technologies, Grand Isle, NY, USA) were used to determine the quality and yield, respectively.…”
Section: Construction and Sequencing Of Small Rna And Degradome Libramentioning
confidence: 99%
“…The primers for the selected target genes were designed using the Beacon Designer software (version 7.7, Premier Biosoft International, Ltd., Palo Alto, CA, USA), and the specific stem-loop primers for the miRNAs were designed as reported previously [33]. The PCR amplifications conditions were according to [23]. The U6 snRNA and 18S rRNA served as the miRNA and target gene endogenous references, respectively.…”
Section: Verification Of Dems and Their Targets By Qrt-pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies about genes related to PaWB have been found, but the mechanisms were still unclear. To get a deeper understanding of the interaction between Paulownia and phytoplasmas, we compared the data obtained in this study with others [51,52]. The number and species of miRNAs or genes in the present study were different.…”
Section: Discussionmentioning
confidence: 99%
“…Rifampicin treatment can make PaWB-infected Paulownia recover to normal morphology [13]. Furthermore, the rapid development of 'omics' has allowed for the investigation of the transcriptomes [3,[14][15][16][17][18], microRNAs (miRNAs), degradomes [19][20][21][22], and proteomes [4,23] of Paulownia species, and the results have revealed changes after PaWB infection at transcriptional, post-transcriptional, and translational levels.…”
Section: Introductionmentioning
confidence: 99%